Understanding school culture via analyzing organizational stories - Celik, Vehbi (Academic Journals, 2010)
Schools have different cultures specific to themselves. School culture represents dominant values, norms, assumptions, beliefs, stories, ceremonies and symbols shared by the members of a school. The objective in interpreting school culture is to understand the stories and symbols created by the members of this culture. Organizational story is a tool to analyze school culture. This article aims to highlight the relationship between organizational stories and school culture. This discussion has been formed with respect to social constructivism, interpretive organizational symbolism and critical theory. Social constructivism, interpretive organizational symbolism and critical theory constitute a multi-disciplinary perspective for organizational story studies. In present research, qualitative research method has been applied. The attempt has been to analyze total 200 stories obtained from ten primary schools. It has been detected that collected stories mostly reflected negative school culture.
Keywords: School culture; organizational stories; organizational learning; analysis organizational stories